2014
DOI: 10.1016/j.fluid.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate nucleation in quiescent and dynamic conditions

Abstract: Gas hydrate nucleation is the spontaneous formation of an ordered crystalline lattice from a disordered phase. This inherently random process often involves long induction times particularly in quiescent conditions. An experimental study was conducted to explore the kinetics of hydrate formation in the presence of mineral grains and when subjected to mechanical agitation. Results show that tetrahydrofuran THF hydrate nucleation is facilitated in the presence of most minerals, and induction times are a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…The decrease in the induction time of gas hydrate formation with the increase in the agitation intensity, which has been observed in a number of studies, can reasonably be attributed to the decrease in each of the identified components of t ind .…”
Section: Effect Of An Increase In Mixing Intensity On the Induction Timesupporting
confidence: 53%
See 1 more Smart Citation
“…The decrease in the induction time of gas hydrate formation with the increase in the agitation intensity, which has been observed in a number of studies, can reasonably be attributed to the decrease in each of the identified components of t ind .…”
Section: Effect Of An Increase In Mixing Intensity On the Induction Timesupporting
confidence: 53%
“…Mechanical agitation is indeed a practical and economic way to decrease the induction time of gas hydrate formation. Nonetheless, the results of studies showing that an increase in agitation intensity leads to a decrease in induction time do not allow general conclusions to be drawn and used to develop mixing strategies that exploit this effect and that can be applied to systems or scales other than the ones used in the studies. First, more often than not, the experimental setups used in these studies consisted of small vessels agitated by a magnetic stirrer bar or, more rarely, by an impeller.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature-time signatures all exhibit a common sequence of characteristic features: induction time, supercooling, or overpressuring prior to phase transformation, exothermic/endothermic transients during phase transformation (Figure 3: test 4. See Dai et al, 2014). P-T trajectories follow phase boundaries when phase transitions are involved, including water-ice, liquid-gas CO 2 , and the hydrate phase boundary (Figure 3: all cases).…”
Section: Results and Observationsmentioning
confidence: 99%
“…However, as revealed by X‐ray CT scanning, all specimens with higher hydrate volume fractions tend to have a relatively uniform hydrate distribution, while the specimens where hydrate accumulates preferentially at the core periphery and grows inwardly in a dendritic pattern have relatively lower hydrate volume fractions (refer to Figure ). The following underlying mechanisms govern these phenomena: Hydrate nucleation is inherently spontaneous and appears to be random in induction time, affected by the thermal history, physical properties, impurities, and mechanical agitation of the solution (Dai et al, ; Mullin, ). Thus, the location and the induction time (or subcooling temperature T sc ) of hydrate nucleation initiation are not predictable.…”
Section: Analyses and Discussionmentioning
confidence: 99%